Acetazolamide triggers death inducing autophagy in T‐47D breast cancer cells. (15th November 2013) - Mohammadpour, Raziye; Safarian, Shahrokh; Ejeian, Fatemeh; Sheikholya‐Lavasani, Zahra; Abdolmohammadi, Mohammad Hossein; Sheinabi, Nader
Abstract The inhibitory effects of acetazolamide on the growth and proliferation of epithelial breast cancer cells (T‐47D) were investigated. Analysis of morphological changes indicated little apoptosis in T‐47D cells incubated with acetazolamide, according to data from flow cytometry, DNA laddering, and expression of AIF. However, an increase in caspase‐3 activity was detected in cells. This was concomitant with an increase in DFF45/DFF40 ratio leading to inhibition of caspase‐3 activity, DNA fragmentation and progression of apoptosis. Flow cytometry also confirmed that acetazolamide had no significant effect on cell cycle progression. These results are consistent with lack of change in the expression of cell cycle regulatory proteins p21, p27, cdc2 and cyclinD1. Increased expression of ATG5, p53 and DRAM, along with an increase in BCLN1/Bcl‐2 ratio, indicated that acetazolamide inhibited the proliferation of T‐47D cells by inducing autophagy. Increased expression of PTEN, along with decreased expression of Akt1, also showed that acetazolamide treatment resulted in death inducing autophagy. Collectively the results indicate that autophagy is an adequate mechanism mediating the anti‐cancer effects of acetazolamide in T‐47D cells through engagement of p53/DRAM pathway and attenuation of Akt survival signalling.